Improving Mathematics Learning Outcomes On Integer Materials Through Think Pair And Share Learning Models - Nurhikmah, Ika; Wibowo, Setiawan Edi; Bafirman, Bafirman (STKIP Singkawang, 2024)
This study aims to: (1) determine the extent to which the Think Pair and Share learning model can improve Mathematics learning outcomes about integers in grade IV students of Nasem Merauke Elementary School, (2) improve mastery of Mathematics learning materials for grade IV students of Nasem Merauke Elementary School, so that student learning outcomes can improve, and (3) reflect on oneself for the sake of improving teacher abilities. This study employed a quantitative approach. This study indicated that fourth-grade students at Inpres Nasem Merauke Elementary School show improved understanding of integers subsequent to the application of the Think Pair and Share instructional style. The proportion of students achieving the learning completion in each cycle, from 17 students (68.00%) in cycle I to 22 students (88.00%) in cycle II, signifying a beneficial impact. The proportion of students who failed to fulfill the prerequisites fell from 8 (32.0%) in cycle I to 3 (12.00%) in cycle II. The Think Pair and Share learning model benefits students by fostering creativity, sustaining their interest in the content, and mitigating the effects of boredom on their learning experience